An efficient removal of power-line interference and baseline wander from ECG signals by employing Fourier decomposition technique. (March 2020) - Singhal, Amit; Singh, Pushpendra; Fatimah, Binish; Pachori, Ram Bilas
Abstract: Baseline wander (BW) and power-line interference (PLI) tend to occur in every recorded electrocardiogram (ECG) signal and can significantly deteriorate the quality of the signal. They need to be separated from the ECG signal to facilitate an accurate diagnosis of the patient. In this paper, we propose a new methodology based on the Fourier decomposition method (FDM) to separate both BW and PLI simultaneously from the recorded ECG signal and obtain clean ECG data. The proposed method employs either of discrete Fourier transform (DFT) or discrete cosine transform (DCT) in order to process the signal. Key DFT/DCT coefficients relating to BW and PLI are identified and then suppressed using optimally designed FDM based on a zero-phase filtering approach. The effectiveness of our method is validated on the MIT-BIH Arrhythmia database. Simulation results clearly demonstrate that the proposed method performs superior in comparison to the existing state-of-the-art techniques at different levels of signal to noise ratio power (SNR). Moreover, this method has low computational complexity which makes it suitable for real-time pre-processing of ECG signals.